Neo-Victorian Presence: Tom Phillips and the Non-Hermeneutic Past - Ferguson, Christine (Australasian Journal of Victorian Studies, 2013)
This essay reads Tom Phillips’s stunning and still in-process artist’s book A Humument (1966-) as exemplar of a non-hermeneutic vein of neo-Victorian textual production that stands as playful foil to the more familiar, suspicion-inflected appropriations of the nineteenth century that have come to dominate the mode’s nascent canon. It places A Humument, the product of a cut-up and OULIPO-esque constrained writing experiment built on an edition of W.H. Mallock’s A Human Document (1892), in a tradition which include Max Ernst’s Une semaine de bonté (1934), Iain Sinclair’s White Chapell, Scarlet Tracings (1987), and non-referential forms of contemporary steampunk performance. What all these examples share is a fascination with what I term, following Hans Gumbrecht, the presence effects of Victorian style and material cultures over their potential hermeneutic significance or value. A Humument not only thwarts the hermeneutic process, but also aestheticises its dislocation through its perpetually changing visual modification of its nineteenth-century original source text. I trace the work’s implications for current debates about the respective value of surface and depth-based approaches to the nineteenth-century text within Victorian studies, and demonstrate how A Humument models a form of non-hermeneutic engagement that retains a keen sense of ethical responsibility towards the past.